Odpowiedzi

2009-04-20T18:58:51+02:00
D) 3(2x+1)-4x≤7(x+4)
6x+3-4x≤7x+28
6x-4x-7x≤28-3
-5x≤25 /÷-5
x≥-5
e) x-1+2(x-2)+3(x-3)>0
x-1+2x-4+3x-9>0
x+2x+3x>1+4+9
6x>14 /÷6
x>14/6
f) x-5/3+1/3 ≥x-6
x-x≥-6+5/3-1/3
0≥-14/3
g)12x-5<3x-5/4
12x-3x<-5/4+5
9x<15/4 /÷9
x< 15/36
2009-04-20T18:59:24+02:00
D) 3(2x+1)-4x≤7(x+4)= 6x+3-4x≤7x+28 = 6x-7x -4x≤28-3= -5x≤25 = x≥-5

e) x-1+2(x-2)+3(x-3)>0= x-1+2x-4+3x-9>0 = x+2x+3x>1+4+9 =6x>14=
x>2 1/7

f) x-5/3+1/3 ≥x-6= x - x≥5/3-1/3-6 = 0≥ -5/3+1/3 ->sprzeczność

g)12x-5<3x-5/4= 12x-3x <-5/4 +5= 9x < 6 1/4 = x<25/36

chyba będzie tak :)
2009-04-20T19:02:29+02:00
D) 3(2x+1)-4x≤7(x+4)
6x+3-4x≤7x+28
2x+3≤7x+28
2x-7x≤28-3
-5x≤25 |:(-5)
x≤-5

e)x-1+2(x-2)+3(x-3)>0
x-1+2x-4+3x-9>0
6x-14>0 |+14
6x>14 |:6
x>2.(3)

f)x-5/3+1/3≥x-6
x-x≥-6+5/3-1/3
0≥4⅔
(nie wiem czy to jest dobrze)

g)12x-5<3x-1¼
12x-3x<-1¼+5
9x<4,25 |:9
x<0,47(2)

prosze... mam nadzieje że dobrze...
jeżeli nie to bardzo przepraszam
2009-04-20T19:03:36+02:00
D) 3(2x+1)-4x≤7(x+4)
6x+3-4x≤7x+28
2x≤7x+25
-5x≤25
x≥5
e) x-1+2(x-2)+3(x-3)>0
x-1+2x-4+3x-9>0
6x-14>0
x>14/6
f) x-5/3+1/3 ≥x-6 /*3
x-5+1≥3x-18
-2x≥-14
x≤7
g)12x-5<3x-5/4
9x<5-5/4
9x<15/4 /*1/9
x<5/12